STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS GAMIFIKASI UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Safroni, Sherli; Hidayah, Ulil (LPPM STAI Muhammadiyah Probolinggo, 2024)
Learning activities cannot be separated from the role of the teacher. The teacher's task is to manage learning in the classroom and use various methods to achieve the learning objectives that have been set. This cannot be separated from the learning model/method used. The aim of this research is to describe the supporting, inhibiting and supporting factors for assessing gamification learning models in Islamic religious education regarding the emotional aspects of students at Madrasah Ibtidaiyah Al-kholili, Probolinggo City. This research uses field research with a qualitative approach. The method used is descriptive research. The subjects of this research were curriculum directors, PAI teachers, and student representatives. Data collection techniques use observation, interviews and documentation. Based on the research results, it can be concluded that the evaluation of the gamification learning model of Islamic religious education on the emotional aspects of students at Al-kholili Islamic Middle School, Probolinggo City can increase student interest and motivation. it has been proven that you can. Children respond to learning, how to complete the tasks given, how to pay attention to the material presented, and the availability of several supporting factors, namely Wi-Fi, depending on possibilities, student interest, teacher motivation and available focus. Children need time to adjust due to inhibiting factors in the form of media and time constraints.